A green and reusable catalytic system based on silicopolyoxotungstovanadates incorporated in a polymeric material for the selective oxidation of sulfides to sulfones - Frenzel, Romina Alejandra (2021)
Two vanadium-containing Keggin silicopolyoxotungsto compounds K5SiVW11O40 and K6SiV2W10O40 were synthesized and characterized. They were incorporated in a superporous hydrogel constitute by prop-2-enamide and propenoic acid as initial monomers and bis-acrylamide as cross-linking moiety. Materials were characterized by several techniques. According to FTIR and 51V MAS-NMR, the (SiVxW12-xO40)(4+x)- anions are the main species present in the hybrid materials. Additionally, they do not decompose during the preparation of the composite. XRD and SEM-EDX results suggest that (SiVxW12-xO40)(4+x)- anions were well dispersed in the support or present as amorphous phases. These materials were evaluated as catalysts in the oxidation of sulfides to sulfones, using an eco-friendly oxidant and mild reaction conditions. The hybrid materials with higher content of the heteropoly compound displayed a remarkable catalytic behaviour in the oxidation of diphenyl sulfide. Materials also exhibited a stable catalytic performance through consecutive reuses. Optimum reaction parameters established were subsequently translated to the oxidation of a sulfide of interest (dapsone) due to its pharmacological activities.